Diseño de un Sendero Interpretativo en las Aguas Termales de Cunuyacu Parroquia Pastocalle, Cantón Latacunga, Provincia De Cotopaxi - Gutiérrez Gutiérrez, María Elizabeth (2015)
The present project proposes the design of the interpretive trail, located in the Pastocalle parish, Latacunga Canton, Cotopaxi province, focused on the management of natural resources, in the potentiation of the same. The interpretive trail called "POLYLEPIS" has an area of 742 metres, consists of eight stops, will be readily accessible, with clear signage for tourists, the tour will be an hour and a half, including interpretive stops and taking pictures. The firm has wide theme that contains a set of regulations and established methods, such as descriptive diagnosis, which is detailed in the field, social, economic, environmental, tourism, the inventory of natural and cultural resources; the development of the project was carried out field visits, resulting in 5 natural sites that were taken into account for the design….